2005
DOI: 10.1038/sj.bmt.1704773
|View full text |Cite
|
Sign up to set email alerts
|

Difference in time to positivity is useful for the diagnosis of catheter-related bloodstream infection in hematopoietic stem cell transplant recipients

Abstract: Summary:Catheter-related bloodstream infections are associated with recognized morbidity and mortality. Accurate diagnosis of such infections results in proper management of patients and in reducing unnecessary removal of catheters. We carried out a prospective study in a bone marrow transplant unit to assess the validity of a test based on the earlier positivity of central venous blood cultures in comparison with peripheral blood cultures for predicting catheter-related bacteremia. Between May 2002 and June 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(18 citation statements)
references
References 23 publications
0
18
0
Order By: Relevance
“…They concluded that surveillance blood cultures were of limited value in predicting infection. Neither this study nor any one of the studies mentioned above utilized differential time to positivity as did Abdelkafi et al [18], who found that marker was associated with 86% sensitivity and 87% specificity. Thus it seems that surveillance blood cultures result in identification of central line colonization status, which does not require treatment.…”
Section: Discussionmentioning
confidence: 64%
“…They concluded that surveillance blood cultures were of limited value in predicting infection. Neither this study nor any one of the studies mentioned above utilized differential time to positivity as did Abdelkafi et al [18], who found that marker was associated with 86% sensitivity and 87% specificity. Thus it seems that surveillance blood cultures result in identification of central line colonization status, which does not require treatment.…”
Section: Discussionmentioning
confidence: 64%
“…If the clinicians have routinely access to the data regarding DTP of pairs of positive blood cultures drawn from a PV and CVL it may serve as a decision support tool for removal of infected CVL. Table illustrates the results of four other studies of the use of DTP in diagnosing CRBSI in a hematologic/oncologic patient population of which two were in a mixed pediatric/adult population . All studies seem to indicate an important potential for differentiating infected and non‐infected CVL from each other in both adults and children by use of DTP before considering removal of a catheter.…”
Section: Discussionmentioning
confidence: 99%
“…However, studies have not specifically addressed the impact of this fi nding on the accuracy of the diagnosis of Candida infections [11]. Only a few patients with Candida infections have been included in most investigations [30][31][32][33]. For example, a study of 204 intensive care unit patients with suspected CVC-associated infection confi rmed 28 infections, 6 of which were caused by Candida species [34].…”
Section: Differential Time To Positivitymentioning
confidence: 97%